The exchange of words speech, testimony, and intersubjectivity - Moran, Richard 1953- (Oxford University Press, 2018)
The capacity to speak is not only the ability to pronounce words, but the socially-recognized capacity to make one's words count in various ways. We rely on this capacity whenever we tell another person something and expect to be believed, and what we learn from others in this way is the basis for most of what we take ourselves to know about the world.